PENDIDIKAN SPIRITUAL PADA ANAK USIA DINI Upaya Penggalian Narasi edukatif al-Quran Dalam Pembinaan Rasa Keagamaan Pada Anak - Rohimin Rohimin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This paper aims  to explore and  elaborate narrative-educational of al-Quran about giving  the  direction of spiritual education of early childhoodmethodology. Spirituality education in early childhood is a spirituality education without tariqah, suluk,  maqam, and murshid. Spiritual education developed in early childhood is a spiritual education that  is dzauqiyah, that  is spirituality that  is perceived and  not rationalized spirituality. Spiritual education is basically building and  developing the  potential divine  nature that  has  been conferred on every human being. The building of spiritual education is the immunization of human beings in order to stay awake and preserved in the circle of homosex- ual religious, that  is the man who covered with religion. From the very beginning creation of man, the Qur’an provides an educative narrative in order to establish and develop a sense of religion, especially in early childhood. This religious sense in turn will provide endurance for humans in tracing its life cycle. Spiritual education through the  guidance of religious sense in early childhood is seen  as a glorious time  to stimulate the nature of the divine  instincts that  already exist in each child. Keywords: Spiritual education, early childhood, narrative-educational, and al-Quran